(untitled) (City: History, Culture, Society, 2020)
According to the “spatial turn,” space in cities are considered not only in the context of social processes but also as a product of human activity and imagination. Street naming is an integral part of the human vision of space in cities. In the medieval and early modern times, the names were inextricably linked to the objects, artisans, or communities residing in the territory. Due to this, I can classify street names and trace their origins. Often, the street naming is mentioned in the renaming directories and studied, mainly, at the local lore level, especially in Lviv. It means that street names in Lviv sometimes became the subject of speculation and have overgrown with centuries-old myths. My research aims to clarify the renaming processes, study the genesis of such names, and display them on a map using a geo-information system. That will explain and makes us better understand their formation. So, I present an advanced methodology of researching street names in Lviv. As the first step in this research, I created a database of the street names in Lviv in 1382-1768 years. The tax records were the primary source, and the city council books were the auxiliary source. In this database, every street name has a unique ID. Then, I created the Geo-informational system [application QGIS 2.18]. It has three layers, where: layer one contains the Friedrich von Mieg’s map of Lviv (XVIII century), layer two has a modern map, and layer three contains the objects (streets), to which names from the database are merged. Because of the ID, the application extracts only the desired street name and chronologically displays its development. It allows us to analyze the changes in street names, their approximate location, and understand the origins of some myths in Lviv’s street naming. For example, analyzing the development of street name “Sutorum/Szewska” (Cobbler street) I have proved that the building and appearance of the Jesuit church have affected to the perception of the adjacent space, so the street name became dual: “Jesuit or Szewska street”. The second example shows that street name “Zarwanska/Serbanska” comes from the old-polish word, which means “loud market”, but not from the Serbians that came to Lviv much later, than street name appeared.